Agarose hydrogel doped with soluble Se-chitosan for Se-enriched cultivation of sprouts - Yun Wang; Wei Yang; Jian Zhu; Qifei Chen; Na Li (Advanced Agrochem, 2023)
Se-chitosan with a high Se content of 139 mg/g was successfully synthesized using the glacial acetic acid-sodium selenite (HAc-Na2SeO3) method. The chemical structure of Se-chitosan was characterized by FTIR, XRD, TGA, UV–vis and 13C NMR, confirming that selenite acid was introduced into chitosan via the esterification reaction of the hydroxyl group at C6 and the electrostatic interaction of the amino group at C2 of chitosan. Agarose hydrogels were designed as an efficient carrier of Se-chitosan for Se-enriched cultivation of sprouts. The hydrogels exhibited a porous structure, which is beneficial for Se diffusion in hydrogels. The growth indexes of sprouts grown in Agar/Se-chitosan composite hydrogels with different Se concentrations, including plant weight, plant height and Se content, were investigated. The results showed that in the Se-enriched cultivation of sprouts, Se-chitosan possessed an excellent Se enrichment effect. As the Se concentration in Agar/Se-chitosan composite hydrogels increases from 0 to 1600 μg/L, the Se content of the sprouts will also increase from 0.92 mg/kg to 6.79 mg/kg accordingly. Moreover, it is necessary to control the amount of Se-chitosan added to the hydrogels; otherwise, the growth of sprouts will be inhibited. This research provided a simple and effective method for the fabrication of Se-containing hydrogels for Se-enriched cultivation of sprouts.